Bioequivalence, safety and immunogenicity of BI 695501, an adalimumab biosimilar candidate, compared with the reference biologic in a randomized, double-blind, active comparator phase I clinical study (VOLTAIRE®-PK) in healthy subjects. (1st December 2016) - Wynne, Christopher; Altendorfer, Mario; Sonderegger, Ivo; Gheyle, Lien; Ellis-Pegler, Rod; Buschke, Susanne; Lang, Benjamin; Assudani, Deepak; Athalye, Sandeep; Czeloth, Niklas
ABSTRACT: Background : This Phase I study (VOLTAIRE®-PK) aimed to evaluate three-way pharmacokinetic similarity (bioequivalence), safety, and immunogenicity of BI 695501 (a Humira® [adalimumab] biosimilar candidate) compared with US- and EU-approved Humira in healthy male subjects. Methods : Subjects ( N  = 327) were randomized 1:1:1 to receive one 40-mg subcutaneous dose of BI 695501, US- or EU-approved Humira; safety was assessed for 70 days. Bioequivalence was evaluated using the average bioequivalence method to test if the 90% confidence intervals (CIs) of the geometric means (BI 695501 vs US- and EU-approved Humira) for the primary end points were within prespecified acceptance ranges (80–125%). Immunogenicity was assessed using a sensitive bridging method. Results : Bioequivalence between BI 695501 and US- and EU-approved Humira was demonstrated with the 90% CIs of the ratios of all primary end points: C max, AUC0–inf, pred and AUC0–tz being within the prespecified acceptance ranges of 80–125%. Concentration vs time profiles were similar as were the time course and frequency of immunogenic responses. All study drugs showed similar safety and tolerability results. Conclusions : Three-way bioequivalence of BI 695501 to US- and EU-approved Humira was demonstrated; safety and immunogenicity results of the three study drugs were also similar. Clinical trial registration : 2013-003722-84 (EudraCT) and NCT02045979.